Comparative Efficacy of Cytokines and Drugs in Promoting the Expansion of Bone Marrow-Derived Mesenchymal Stem Cells: A Systematic Review and Meta-Analysis - Liu, Jinhui; Liu, Sheng; Li, Chunming (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background Bone Marrow (BM) Mesenchymal Stem Cells (MSCs) possess significant clinical potential, yet their limited expansion ability in the laboratory restricts their broad application. While cytokines and pharmaceuticals are commonly used strategies to promote BM-MSC expansion, a systematic comparison of their effects has not been conducted. This study aims to evaluate and compare the effects of cytokines and pharmaceutical agents on the proliferation and osteogenic differentiation of BM-MSCs through a comprehensive review and meta-analysis. Materials and Methods A comprehensive search was performed across PubMed and Web of Science to identify 15 quantitative studies comparing the efficacy of cytokines or pharmaceutical agents against control groups in enhancing BM-MSC proliferation or osteogenic differentiation. A meta-analysis was conducted to assess the pooled effect sizes of cytokines and pharmaceuticals. Results Meta-analysis revealed a significant enhancement in BM-MSC proliferation with both cytokines (SMD=1.42) and drugs (SMD=1.28), as well as in osteogenic differentiation (SMD=1.65 and 1.51). Subgroup analysis identified specific cytokines, such as LIGHT, IL-17A, IL-6, TGF-β1, BMP-2/7, and drugs including melatonin, HDAC inhibitors, AMPK activators, and artemisinin, as having significant promoting effects on BM-MSC expansion. Conclusion This research validates the efficacy of both cytokines and pharmaceutical agents in enhancing BM-MSC expansion, despite limitations such as heterogeneity in study design and reporting quality. The findings provide valuable insights for fundamental and translational BM-MSC research. Future studies could explore the combined use of these two methods to develop safer and more effective strategies for increasing BM-MSC numbers.
Keywords: Bone Marrow-Derived Mesenchymal Stem Cells; Cytokines; Drugs; Proliferation; Osteogenic Differentiation; Systematic Review; Meta-Analysis